2010
DOI: 10.1016/j.intcom.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Using a touch screen computer to support relationships between people with dementia and caregivers

Abstract: a b s t r a c tProgressive and irreversible cognitive impairments affect the ability of people with dementia to communicate and interact with caregivers. This places a burden on caregivers to initiate and manage interactions to the extent that they may avoid all but essential communication. CIRCA is an interactive, multimedia touch screen system that contains a wide range of stimuli to prompt reminiscing. The intention is that people with dementia and caregivers will explore CIRCA together, using the recollect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
220
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(249 citation statements)
references
References 27 publications
8
220
0
10
Order By: Relevance
“…Some researchers have already shown that joint-attention benefits patient-caregiver communication and relationships (e.g. Astell et al, 2010;Sävenstedt et al, 2005), but to our knowledge the role of joint-attention in performing everyday tasks in people with dementia has not been studied, and warrants attention.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some researchers have already shown that joint-attention benefits patient-caregiver communication and relationships (e.g. Astell et al, 2010;Sävenstedt et al, 2005), but to our knowledge the role of joint-attention in performing everyday tasks in people with dementia has not been studied, and warrants attention.…”
Section: Discussionmentioning
confidence: 94%
“…Second, this strategy would encourage joint attention (a shared focus of two individuals on an object or task). Joint attention is widely studied in developmental psychology (see Striano & Reid, 2006, for a review), but recently dementia care research has shown an interest in it too (Astell et al, 2010;Sävenstedt, Zingmark, Hydén, & Brulin, 2005). The two latter studies show that people with dementia are capable of engaging in joint attention and can benefit from dementia care interventions that utilise joint attention.…”
Section: Third Person Instruction Is An Interesting Proposition For Amentioning
confidence: 99%
“…Caregivers reported in interviews after the two reminiscence activities that they found the traditional sessions much more demanding and that twenty minutes felt like a long time. By contrast they found it relatively easy to facilitate a shared interaction using CIRCA [5]. Lower levels of initiation were recorded for people with dementia in the traditional sessions compared to CIRCA sessions.…”
Section: Outcomes With Circamentioning
confidence: 88%
“…CIRCA is a multimedia computer system developed to make possible again freeflowing conversation between people with dementia and caregivers [1][2][3][4][5]. The system is based on presenting reminiscence materials from a wide range of archives.…”
Section: Supporting Free-flowing Conversation Through Reminiscencementioning
confidence: 99%
“…However, existing products, systems and services are often too complex to be used by PWD [4]. The usability and adaptability of newly designed innovations therefore deserves more attention.…”
Section: Introductionmentioning
confidence: 99%